THE REFLECTION OF RACISM TOWARDS AFRICAN AMERICAN IN SELMA MOVIE - Rahmatillah, Yusrina; Kuncara, Singgih Daru; Nasrullah, Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The purpose of this research is to find the level of racism that happened to African American as seen in Selma movie. Further, the other purpose is to give the reflection about the effect of the racism toward African-American people as depicted in the movie. This research focused to examine the racism by using Jones’ and Day’s theory about the level of racism and on how the effect of racism itself. Further, the researcher used qualitative-descriptive method and Mikos’ data analysis for the movie. In this movie, the researcher finds the three levels of racism have appeared. The racisms are institutionalized racism, personally mediated racism and internalized racism. The first level which is institutionalized racism is marked by the legitimize and systematic intimidation in voting booths. Further, this racism gives positive and negative effect.  Secondly, the personally mediated racism also appeared and it is shown by the limitedness of public access, police brutality and everyday avoidance towards black people. Thus, personally mediated racism also gives positive and negative effect. The last level of racism which appeared in this movie is internalized racism. This racism marked by the acceptance of stigma from white people to black people. Additionally, this racism only gives negative effect because it makes the victim of racism felt insecure, unworthy, and disbelief towards themselves.